An extensive molecular phylogeny of weaverbirds (Aves: Ploceidae) unveils broad nonmonophyly of traditional genera and new relationships. (12th June 2019) - De Silva, Thilina N; Peterson, A Townsend; Perktas, Utku
Abstract: The diverse Old World avian family Ploceidae (weaverbirds) presently comprises 117 species in 17 genera. Despite being a well-known bird group, the family has received incomplete attention in terms of molecular systematics; systematists have often focused on subclades, with the most extensive study to date covering <66% of recognized species. As a consequence, weaverbird taxonomy remains outdated, and phylogenetic relationships, particularly of the African Malimbus (previously Ploceus and Malimbus ) clade, remains largely unresolved. Here, we sampled 109 weaver species (and numerous nominal subspecies), including 99 of the 103 recognized "typical weaverbird" taxa for an 8-gene dataset. Antique DNA techniques were used to extract DNA from study skins of 27 rare taxa not available in global tissue collections. The study included 32 species and 4 genera of ploceids previously unstudied phylogenetically. Our analyses supported monophyly of the family and identified 8 distinct clades. Our results conflict extensively with current taxonomy. We suggest that plumage traits and morphology exhibit high plasticity, such that phenotype does not always reflect phylogenetic relationships in weaverbirds. We recommend (1) uniting African- Ploceus, Malimbus, Anaplectes, and Notiospiza in Malimbus ; (2) retaining the monotypic genus Pachyphantes ; and (3) placing Brachycop e with Euplectes . This study, the first near-species-level phylogeny for the family, lays a firm foundation for downstream studies of biogeography and character evolution.